2019
DOI: 10.1021/acsami.9b09713
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Cathode Catalyst Layer of a Passive Direct Methanol Fuel Cell with Highly Hydrophilic Carbon Aerogel for Improved Water Management

Abstract: Nitrogen-doped porous carbon materials show excellent water adsorption ability by forming strong hydrogen bonding between water molecules and the doped atoms. When these porous carbon materials are used to construct a water management layer (WML) of a passive direct methanol fuel cell (DMFC), high water concentration and hydraulic pressure formed inside the cathode catalyst layer would facilitate the water recovery from cathode to anode. In this paper, a highly hydrophilic nitrogen-doped carbon aerogel was syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 40 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…The facile synthesis of nitrogen‐doped carbon catalysts was as follows 41 . A 4.0 mL GO with 5% mass fraction, 16.0 mL water, 0.665 mL formaldehyde with 37% mass fraction, and 0.495 g resorcinol were mixed in sequence and stirred at 300 rpm for over 0.5 hour.…”
Section: Methodsmentioning
confidence: 99%
“…The facile synthesis of nitrogen‐doped carbon catalysts was as follows 41 . A 4.0 mL GO with 5% mass fraction, 16.0 mL water, 0.665 mL formaldehyde with 37% mass fraction, and 0.495 g resorcinol were mixed in sequence and stirred at 300 rpm for over 0.5 hour.…”
Section: Methodsmentioning
confidence: 99%
“…In a study, using the Sessile-drop method, it is observed that decreasing hydrophobicity leads to a small contact angle of water droplets in the GDL fibers [215]. Despite the irreversible performance reduction, there is a chance that the physical degradation of electrodes, especially the cathode, will have implications for water drainage characteristics during a prolonged test, potentially increasing the water flooding conflict [216]. However, the number of lite is limited with linked water flooding behavior to morphological alterations in the CCL during protracted DMFC operation.…”
Section: Influence Of Water Flooding In Mea Degradationmentioning
confidence: 99%
“…Fig. 1 [22] shows the schematic setup of a direct methanol FC or DMFC. A microwave-assisted polyol process was used by Hong Zhu et al [23] to synthesize Pt-Au based on carbon aerogel (CA).…”
Section: Carbon Aerogelsmentioning
confidence: 99%
“…Fig. 2 [22] shows water flooding at cathode current collectors, a challenging problem in the working of a DMFC.…”
Section: Carbon Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation